Looking into the Challenges of Complex IT Projects. - Glass, Robert L. (Communications of the ACM, 2006)
The article focuses on project management for information technology (IT) projects. The author comments on a report issued by the British Royal Academy of Engineering and the British Computer Society focusing on the education of computer programmers and project managers; the study also looked at the management of large-scale IT projects. The author believes that computer programmers are well trained and professional; however, he also mentions that academic programs do not closely reflect business needs. The author believes that project management is difficult to teach and that IT project management is neither better nor worse than other large business projects.